Comparison of Design Guidelines for Hot-Rolled I-Shaped Steel Compression Members according to AISC 360-16 and EC3 - S. Pinarbasi; T. Genc; E. Akpinar; F. Okay (Advances in Civil Engineering)
Thirty-six years after its publication, Turkish Building Code for Steel Structures was replaced with a more rational specification, Specification of Design and Construction of Steel Structures (SDCSS), which was prepared almost entirely based on the current American steel design specification (AISC 360-16). European steel design specification (EC3) is also widely used in Turkey for the design of steel structures constructed with the collaboration of Turkish and European companies. It is essential for a steel designer using both SDCSS and EC3 to comprehend the basic differences between these specifications. This study aims to compare the design guidelines defined in AISC 360-16 (so in SDCSS) and EC3 for rolled I-shaped steel members subjected to axial compression thoroughly. For various steel grades, member lengths, and 153 different European I/H sections, design buckling resistances and design compressive strengths are computed and compared. It is shown that there are at most 3% difference between the effective areas computed using both specifications. It is highly recommended that the change of cross section class be allowed while calculating design buckling resistances. For the studied sections and steel grades, the resistance-to-strength ratios are found to be as high as 1.24 but not smaller than 0.907.